Breakthrough curve analysis for column dynamics sorption of Mn(II) ions from wastewater by using mangostana garcinia peel-based granular-activated carbon - Chowdhury, Z.Z.; Khalifah Sidik, K.; Rashid, K.; Rafique, R.F.; Zain, Sharifuddin Md (2013)
The potential of granular-activated carbon (GAC) derived from agrowaste of Mangostene (Mangostana garcinia) fruit peel was investigated in batch and fixed bed system as a replacement of current expensive methods for treating wastewater contaminated by manganese, Mn(II) cations. Batch equilibrium data was analyzed by Langmuir, Freundlich, and Temkin isotherm models at different temperatures. The effect of inlet metal ion concentration (50 mg/L, 70 mg/L, and 100 mg/L), feed flow rate (1 mL/min and 3 mL/min), and activated carbon bed height (4.5 cm and 3 cm) on the breakthrough characteristics of the fixed bed sorption system were determined. The adsorption data were fitted with well-established column models, namely, Thomas, Yoon-Nelson, and Adams-Bohart. The results were best-fitted with Thomas and Yoon-Nelson models rather than Adams-Bohart model for all conditions. The column had been regenerated and reused consecutively for five cycles. The results demonstrated that the prepared activated carbon was suitable for removal of Mn(II) ions from wastewater using batch as well as fixed bed sorption system.